2016
DOI: 10.1117/1.jbo.21.12.120502
|View full text |Cite
|
Sign up to set email alerts
|

In vivo super-resolution retinal imaging through virtually structured detection

Abstract: In vivo super-resolution retinal imaging through virtually structured detection,"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…36 Time-lapse microscopy of freshly isolated photoreceptor outer segments confirmed that the transient outer segment change occurs almost immediately after the stimulus onset, 32,33,35 which is consistent to the time course of fast photoreceptor-IOS in functional OCT (Figure 8). By developing a virtually structure detection (VSD) based super-resolution laser scanning ophthalmoscope (SLO), 37 in vivo super-resolution imaging of transient retinal photoreceptor movement evoked by oblique light stimulation has also been demonstrated ( Figure 10). 38 In addition to the fast photoreceptor-IOS, slow IOS changes were also observed at inner retinal layers.…”
Section: Discussionmentioning
confidence: 99%
“…36 Time-lapse microscopy of freshly isolated photoreceptor outer segments confirmed that the transient outer segment change occurs almost immediately after the stimulus onset, 32,33,35 which is consistent to the time course of fast photoreceptor-IOS in functional OCT (Figure 8). By developing a virtually structure detection (VSD) based super-resolution laser scanning ophthalmoscope (SLO), 37 in vivo super-resolution imaging of transient retinal photoreceptor movement evoked by oblique light stimulation has also been demonstrated ( Figure 10). 38 In addition to the fast photoreceptor-IOS, slow IOS changes were also observed at inner retinal layers.…”
Section: Discussionmentioning
confidence: 99%
“…24 Recently, we demonstrated the feasibility of the line-scanning strategy for rapid VSD-based super-resolution imaging of both isolated retinas 25 and intact frog eyes. 26,27 Figure 4 shows the experimental setup and representative in vivo super-resolution images captured with 127 frames/s speed. As shown in Figure 4(b), the VSD-based SLO enabled unambiguous observation of individual retinal photoreceptors (Figure 4(b1)) and ganglion fibers (Figure 4(b2)).…”
Section: In Vivo Super-resolution Ophthalmoscopy Of Animal Retinasmentioning
confidence: 99%
“…As shown in Figure 4(b), the VSD-based SLO enabled unambiguous observation of individual retinal photoreceptors (Figure 4(b1)) and ganglion fibers (Figure 4(b2)). 26 By providing high-spatial (µm) and high-temporal (∼10 ms) resolutions, the VSD-based super-resolution SLO has been used to validate in vivo monitoring of transient retinal phototropism evoked by oblique light stimulation. 27…”
Section: In Vivo Super-resolution Ophthalmoscopy Of Animal Retinasmentioning
confidence: 99%
“…Here, we demonstrated for the first time in vivo observation of TRP using a custom-designed super-resolution ophthalmoscope [20]. The custom-built digital ophthalmoscope employed virtually structured detection (VSD) to achieve a sub-cellular level of spatial resolution, and it combined a rapid line-scanning strategy to realize a millisecond level of temporal resolution.…”
Section: Introductionmentioning
confidence: 99%